'Pizza every day – why?': A survey to evaluate the impact of COVID‐19 guidelines on secondary school food provision in the UK. Issue 2 (4th June 2021) - Rose, Kelly; O'Malley, Claire; Brown, Laura; Ells, Louisa Jane; Lake, Amelia A.
Abstract: The nutritional requirements of adolescence and the reported poor UK eating behaviours of young people are a significant public health concern. Schools are recognised as an effective 'place' setting to enable improvement to nutrition outcomes. The COVID‐19 pandemic resulted in UK school closures from March 2020. In re‐opening in September 2020, schools were required to meet guidelines to ensure the minimised impact of COVID‐19 on the population (DfE 2020). We aimed to evaluate the impact of COVID‐19 school guidelines on secondary and post‐16 (16–18 years) food provision. An online survey was posted on 8th October to 1st December 2020, targeted at young people, parents and staff of secondary/post‐16 education establishments in the UK. Two hundred and fifty‐two responses were received, of which 91% reported a change in their school food provision, 77% reported time for lunch was shortened and 44% indicated the provision was perceived as less healthy during September 2020 (post‐lockdown school return) compared with March 2020 (pre‐lockdown). Analyses demonstrated that time, limited choice and healthiness impacted negatively upon young people's school food experience. The COVID‐19 pandemic has presented a huge challenge to the delivery of healthy school food to young people. Therefore, schools require more support in following national food standards and incorporating nutrition education and behaviour change strategies within current guidelines.